Nitric Oxide Concentration and Other Salivary Changes after Insertion of New Complete Dentures in Edentulous Subjects - Maria de Lourdes Breseghelo; Lídia Andreu Guillo; Túlio Eduardo Nogueira; Cláudio Rodrigues Leles (International Journal of Dentistry)
Objective. To assess changes in levels of salivary nitric oxide (NO) after insertion of new complete dentures and its association with clinical and salivary parameters. Methods. Nineteen fully edentulous subjects were included, mean age 64.4. Unstimulated whole saliva was collected before and after insertion of the dentures, at follow-up visits, and after 12 months. The concentration of the final stable NO product (nitrite) was measured by a colorimetric assay based on the Griess reaction. Clinical parameters were assessed during all clinical visits. Results. Functional adaptation to the dentures progressively improved, with no complaints at the long-term follow-up. NO concentration was not influenced by the level of functional adaptation, presence of injuries to the mucosa, salivary flow, and saliva viscosity. Pairwise comparison showed a reduction in NO concentration at the first follow-up compared to baseline values but differences were not statistically significant. Significant differences were observed in NO concentrations at the long-term follow-up when compared to the first (p=0.024) and second (p=0.027) visits. Conclusion. NO concentration reduced after denture insertion and returned to baseline levels in the long-term follow-up. This appears to be an autonomic response of the body and provides valuable complementary information for the management of the edentulous patient.